A Novel Solar Driven Photocatalyst: Well-Aligned Anodic WO3 Nanotubes - Chin, Wei Lai; Abd Hamid, Sharifah Bee; Sreekantan, Srimala (Hindawi Publishing Corporation, 2013)
Well-aligned anodic tungsten trioxide (WO3) nanotubes were successfully synthesized by anodization of W foil at 40V in a bath with electrolyte composed of 1M of sodium sulphate (Na2SO4) and 0.5 wt% ammonium fluoride (NH4F). The effect of electrochemical anodization times on the formation mechanism of anodic WO3 nanotubular structure was investigated. It was found that minimumof 15 min is required for completing transformation fromWfoil toWO3 nanotubular structurewith an average diameter of 50nmand length of 500 nm.Thephotocatalytic ability of the sampleswas evaluated by degradation of methyl blue (MB) dye.Theresults indicate that the surface morphology of anodicWO3 affected the photocatalyticMBdegradation significantly under solar illumination.